2018
DOI: 10.1016/j.watres.2018.05.046
|View full text |Cite
|
Sign up to set email alerts
|

The role of salinity on the changes of the biomass characteristics and on the performance of an OMBR treating tannery wastewater

Abstract: Tannery wastewaters are difficult to treat biologically due to the high salinity and organic matter concentration. Conventional treatments, like sequential batch reactors (SBR) and membrane bioreactors (MBR), have showed settling problems, in the case of SBR, and ultrafiltration (UF) membrane fouling in the case of MBR, slowing their industrial application. In this work, the treatment of tannery wastewater with an osmotic membrane bioreactor (OMBR) is assessed. Forward osmosis (FO) membranes are characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Focusing on bacteria affecting nitrogen processing, Halomonas and Azoarcus were abundant and clustered in the community heatmap analysis across all phases. The genera most frequently identified among the 10 experimental phases were Cohaesibacter, Marinobacter, and Halomonas, which have been found in marine environments [61,62]. The most dominant genera in phase H4_N50 were Rhodobacteraceae (13.7%), Fusibacter (8.0%), and Halomonas (6.6%), while the dominant ones changed to Cohaesibacter (17.7%) and Labrenzia (7.1%) in H7_N150.…”
Section: Bacterial Community Composition At the Phylum And Genus Levelsmentioning
confidence: 99%
“…Focusing on bacteria affecting nitrogen processing, Halomonas and Azoarcus were abundant and clustered in the community heatmap analysis across all phases. The genera most frequently identified among the 10 experimental phases were Cohaesibacter, Marinobacter, and Halomonas, which have been found in marine environments [61,62]. The most dominant genera in phase H4_N50 were Rhodobacteraceae (13.7%), Fusibacter (8.0%), and Halomonas (6.6%), while the dominant ones changed to Cohaesibacter (17.7%) and Labrenzia (7.1%) in H7_N150.…”
Section: Bacterial Community Composition At the Phylum And Genus Levelsmentioning
confidence: 99%
“…The underlying assumption that lipid hydrolysis is mediated mostly by microbial enzymes and not by physico-chemical processes in the wastewater treatment system, might be incorrect. However, an extensive body of research on aerobic municipal wastewater treatment (Molina-Muñoz et al 2010;Cortés-lorenzo et al 2012;Calderón et al 2013;Ferrer-polonio et al 2018), anaerobic municipal wastewater treatment (Petropoulos et al 2018) and industrial wastewater treatment (Silva-bedoya et al 2016;Luján-Facundo et al 2018) has been published to corroborate the assumption of enzymatic lipid hydrolysis. It should be noted that this prior research was most often conducted with p-nitrophenol synthetic substrates, which target both true lipases, hydrolyzing triacylglycerol lipids, and esterases, hydrolyzing several types of ester bonds.…”
Section: Lipid Hydrolysis Monitoring With a Vegetable Oil -Rhodamine mentioning
confidence: 99%
“…Their result indicated that the OMBR system showed low membrane fouling tendency and high water flux with this draw solution. In another study by Luján-Facundo et al [ 97 ], they used the same wastewater as the draw solution to treat tannery wastewater which contained high salinity and organic matter concentration in an OMBR system. Although the reverse salt flux was mitigated by using this new draw solution, the salt accumulation was also observed due to the dewatering process of the naturally high-salinity wastewater.…”
Section: Integration Of Fo With Other Wastewater Treatment Technologiesmentioning
confidence: 99%